Targeted neonatal echocardiography and lung ultrasound in preterm infants with chronic lung disease with and without pulmonary hypertension, screened using a standardized algorithm - Sánchez-Becerra, Janneth Cristina; Guillén-Torres, Rogelio; Becerra-Becerra, Rosario; Márquez-González, Horacio; Ibarra-Ríos, Daniel (Frontiers in Pediatrics, 2023)
Introduction Increased recognition of the development of chronic pulmonary hypertension (cPH) in preterm infants with chronic lung disease (CLD) has prompted enhanced monitoring for the identification of different phenotypes. Methods All newborns consulted for oxygen/respiratory support dependency (CLD assessment) from January 2018 to December 2021 were included. TnECHO and LUS screening for cPH-CLD were performed at 36 weeks postmenstrual age. Cases of cPH related to increased pulmonary blood flow (cPH-IPBF) were referred to Pediatric Cardiology. The objective of the study was to identify all cases of cPH (cPH-CLD/IPBF) in the CLD patients screened and to compare outcomes. Following a standardized algorithm, cPH-CLD patients were treated with diuretics; ultrasounds taken before and after treatment were analyzed. Results Seventy-two patients with CLD were screened. Twenty-two (30%) had cPH-CLD, and nine (12%) had cPH-IPBF. cPH infants underwent more days of mechanical ventilation, were more likely to have retinopathy of prematurity, and showed increased mortality. The LUS pattern observed in the 72 CLD patients consisted of a thickened pleural line and a B-line interstitial heterogeneous pattern; 29% of patients were found to have lung consolidations. After diuretic therapy, step-down in respiratory support occurred in 59% of neonates with cPH-CLD. A decrease in respiratory rate (RR), right ventricular output (RVO), markers of pulmonary vascular resistance (PVR), and B-line pattern was observed. In tissue Doppler imaging, biventricular diastolic function was found to be modified after diuretics. Conclusions CLD infants with cPH showed increased morbidity and mortality. In cPH-CLD patients, a decrease in RR and step-down in respiratory support was observed after diuretic treatment. Follow-up ultrasound showed a decrease in RVO, markers of PVR, and B-lines.